(3Yde GbJUGOjGJ GdJYdje GdMOjK (B/s - (3YGHOjf, eMehO YHGSs ((3GdbGgQI(B: s (3GdOGQ GdeUQjI GddHfGfjI(B, s, 2000)
(3Yde GbJUGOjGJ GdJYdje(B: (3GdfTCI hGdJYQja, hJWhQ GdeLGdGJ ,YhGFO GdJYdje Hjf GdVjb hGdTGed,JMdjd GdcdaI(B-(3GdaYGdjI hGdENJjGQ Hjf HOGFd GdSjGSI GdJQHhjI,OGdI GdEfJGL GdJQHhj hGdESJNOGe GdCeKd ddehGQO GdJQHhjI,GdLhOI hGbJUGOjGJgG aj GdJQHjIs
Keywords: (3GdJYdje(B- (3GbJUGOjGJs